Oral Health Management Diagnosis Guidelines to support healthcare planning (Research, Society and Development, 2021)
The objective of this study was to present and evaluate the use of the Oral Health Management Diagnosis Guidelines (OHMDG) to support professionals and managers in healthcare planning. The OHMDG was developed with participation of professors, health professionals and policy makers and posteriorly, applied on 4 stages of Oral Health Management Qualification Course, between 2012 and 2019, in 80% municipalities of Paraná State. The participants of the second, third and fourth stages evaluated the OHMDG by electronic form. The approved version of OHMDG consisted of 3 pillars, subdivided into six components, with 3 different scenarios (poor, fair and ideal). The mean score obtained in evaluation of OHMDG was 8.53+ 1.52; 8.0 + 1.65; 8.48 + 1.46, corresponding to stages 2, 3 and 4, respectively. It is concluded that the OHMDG was a tool well evaluated by health professionals to local diagnose and construction of new strategies for improvement of oral health.